Dynamics of acquisition and loss of carriage of Staphylococcus aureus strains in the community: the effect of clonal complex. - Miller, R; Walker, A; Godwin, H; Fung, R; Votintseva, A; Bowden, R; Mant, D; Peto, T; Crook, D; Knox, K (2014)
BACKGROUND: Staphylococcus aureus nasal carriage increases infection risk. However, few studies have investigated S. aureus acquisition/loss over >1 year, and fewer still used molecular typing. METHODS: 1123 adults attending five Oxfordshire general practices had nasal swabs taken. 571 were re-swabbed after one month then every two months for median two years. All S. aureus isolates were spa-typed. Risk factors were collected from interviews and medical records. RESULTS: 32% carried S. aureus at recruitment (<1% MRSA). Rates of spa-type acquisition were similar in participants S. aureus positive (1.4%/month) and negative (1.8%/month, P = 0.13) at recruitment. Rates were faster in those carrying clonal complex (CC)15 (adjusted (a)P = 0.03) or CC8 (including USA300) (aP = 0.001) at recruitment versus other CCs. 157/274 (57%) participants S. aureus positive at recruitment returning ≥ 12 swabs carried S. aureus consistently, of whom 135 carried the same spa-type. CC22 (including EMRSA-15) was more prevalent in long-term than intermittent spa-type carriers (aP = 0.03). Antibiotics transiently reduced carriage, but no other modifiable risk factors were found. CONCLUSIONS: Both transient and longer-term carriage exist; however, the approximately constant rates of S. aureus gain and loss suggest that 'never' or truly 'persistent' carriage are rare. Long-term carriage varies by strain, offering new explanations for the success of certain S. aureus clones.